The influence of intergranular and interphase boundaries and δ-ferrite volume fraction on hydrogen embrittlement of high-nitrogen steel. (26th August 2021) - Panchenko, M.Yu.; Melnikov, E.V.; Mikhno, A.S.; Maier, G.G.; Astafurov, S.V.; Moskvina, V.A.; Reunova, K.A.; Galchenko, N.K.; Astafurova, E.G.
Abstract: We study the effect of grain size of austenitic and ferritic phases and volume fraction of δ-ferrite, which were obtained in different solution-treatment regimes (at 1050, 1100, 1150 and 1200 °C), on hydrogen embrittlement of high-nitrogen steel (HNS). The amount of dissolved hydrogen is similar for the specimens with different densities of interphase (γ-austenite/δ-ferrite) and intergranular (γ-austenite/γ-austenite, δ-ferrite/δ-ferrite) boundaries. Despite, the susceptibility of the specimens to hydrogen embrittlement, depth of the hydrogen-assisted surface layers, hydrogen transport during tensile tests and mechanisms of the hydrogen-induced brittle fracture all depend on grain size and ferrite content. The highest hydrogen embrittlement index IH  = 32%, the widest hydrogen-affected layer and a pronounced solid-solution hardening by hydrogen atoms is typical of the specimens with the lowest fraction of the boundaries. Even though fast hydrogen transport via coarse ferritic grains provides longer diffusion paths during H-changing, the width of the H-affected surface layer in the dual-phase structure of the HNS specimens is mainly determined by the hydrogen diffusivity in austenite. In tension, hydrogen transport with dislocations increases with the decrease in density of boundaries due to the longer dislocation free path, but stress-assisted diffusion transport does not depend on grain size and ferrite fraction. The contribution from intergranular fracture increases with an increase in the density of intergranular and interphase boundaries. Graphical abstract: Image 1 Highlights: Increase in grain size and δ-ferritecontent assists H-embrittlement ofHNS. Coarse ferritic grains provide longer diffusion paths during H-changing. Overall H-affected surface layer is mainly determined by H-diffusivity in austenite. In tension, increase in grain size facilitates hydrogen transport with dislocations. Grain refinement contributes H-assisted intergranular fracture.